Monolithic arrays of silicon sensors - Harding, Ian; Chen, Wei; Giacomini, Gabriele; Kuczewski, Anthony; Rumaiz, Abdul K.; Siddons, David Peter (Frontiers in Physics, 2022)
Monolithic arrays of silicon p-n junctions are commonly used to deliver spatial information on impinging radiation, with the advantages of low-noise and fast signal generation. Additionally, array geometries also allow for a segmentation of a large area into individual channels that can be read out in parallel, so that a high-event rate can be managed. To optimize the noise performance, however, a few points must be addressed to control the silicon/silicon oxide interface. Replacing the p-n junctions with silicon drift sensors avoids noise related to the interface states, at the expense of a more complicated process and slower signals. In this paper, some points needing consideration when engineering a monolithic array of silicon sensor are reviewed.